Behavioural intention determinants of business takaful adoption among microenterprises - Noh, Mohd Khairul Ariff; Ismail, Norashikin; Jaini, Azila; Othman, Nor Azairiah Fatimah (UiTM Cawangan Johor, 2025)
The research explores the factors that affect microenterprises' decision to participate in business Takaful using the Theory of Planned Behaviour framework (TPB). Individual behaviour mostly stems from three critical constructs according to the TPB theory, which include attitudes (ATT), subjective norms (SN), and perceived behavioural control (PBC). An analysis of a dataset from microenterprise owners was conducted using Partial Least Squares Structural Equation Modelling (PLS-SEM) to examine their intentions (INT) to participate in general business takaful products. The study results found PBC to be the strongest indicator of INT, which demonstrates that microenterprise owners with higher control beliefs toward adopting general business takaful are more likely to show intention to participate. The factors of ATT and SN appeared non-significant for predicting INT, so personal beliefs about takaful and social pressures exert minimal influence in this context, even though theory suggests otherwise. The research produces significant results that guide policymakers and practitioners who want to build up general business takaful adoption among microenterprises. Stakeholders should utilise their knowledge about the central position of perceived behavioural control to create specific interventions that build up microenterprise owners' capabilities to enhance Takaful's business participation. Research develops existing knowledge on general business takaful participation and microenterprise development through an assessment of psychological elements affecting financial decisions within this sector. The study demonstrates the requirement for an unobtrusive approach to promote takaful because owners of microenterprises need improved perceived behavioural control to boost adoption rates. Future studies should investigate further variables that could affect Takaful adoption, as well as the possible influence of other interventions and contextual elements on the TPB framework in the domain of Islamic finance. Keywords: Business Takaful, Microenterprises, Partial Least Squares Structural Equation Modelling, Perceived Behavioural Control, Theory of Planned Behaviour